2018
DOI: 10.1159/000489688
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA Attenuates Contrast-Induced Nephropathy via Nrf2 Activation in Rats

Abstract: Background/Aims: Tanshinone IIA is a chemical compound extracted from Salvia miltiorrhiza Bunge, a perennial plant also known as red sage used in traditional Chinese medicine. Tanshinone IIA has been shown to protect against various organ injuries. In this study, we hypothesized that Tanshinone IIA could play an anti-oxidative role in contrast-induced nephropathy (CIN) through enhancing Nrf2/ARE activation. Methods: To test whether Tanshinone IIA can attenuate CIN, oxidative stress, and apoptosis, we utilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 31 publications
1
27
0
1
Order By: Relevance
“…The levels of BUN and SCR were higher in the ioversol-treated group than in the control group. Significantly, similar results were obtained in vitro using HK-2 cells and were consistent with a previously published study [25]. Like the earlier report, our study also showed that pretreatment with t-BHQ, an agonist of Nrf2, could mitigate oxidative stress and alleviate the progression of AKI.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The levels of BUN and SCR were higher in the ioversol-treated group than in the control group. Significantly, similar results were obtained in vitro using HK-2 cells and were consistent with a previously published study [25]. Like the earlier report, our study also showed that pretreatment with t-BHQ, an agonist of Nrf2, could mitigate oxidative stress and alleviate the progression of AKI.…”
Section: Discussionsupporting
confidence: 93%
“…Nrf2 is an important transcription factor belonging to the E26 transformation-specific (ETS) factor family that regulates the cellular resistance to oxidants, including radiocontrast agents [26]. Previous studies have shown that Nrf2 plays a renoprotective role in CIN [25,27]. Sirt3, which is an NAD + -dependent deacetylase localized in the mitochondrial matrix, regulates a variety of cellular processes, including oxidative stress, ATP generation, and energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] The tanshinones consist of four major constituents, such as tanshinone Ⅰ (Tan-Ⅰ), tanshinone IIA, crytotanshinone and dihydrotanshinone Ⅰ, and their biological effects have been a prime research focus. [11][12][13][14] The major constituents of Dan-shen have been recently shown to possess some activities against human cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial cells generate numerous reactive oxygen species during the ischemia-reperfusion process and increase TNF-α synthesis, which can lead to an increase in the apoptosis cascade reaction, the interactions between inflammatory and endothelial cells and intracellular calcium overload (22). Various novel antioxidants have been associated with renal protection through the antioxidative and antiapoptotic pathways (23,24). A previous study (9) has demonstrated that adropin is negatively correlated with the inflammatory marker C reactive protein.…”
Section: Discussionmentioning
confidence: 99%